Climate change and tuberculosis: an analytical framework - Saunders, Matthew J; Boccia, Delia; Khan, Palwasha Y; Goscé, Lara; Gasparrini, Antonio; Clark, Rebecca A; Pescarini, Julia M; Charalambous, Salome; Fekadu, Lelisa; Dockhorn da Costa Johansen, Fernanda; Vasilyeva, Irina; Narendran, Gopalan; et al. (The lancet respiratory medicine, 2025)
Climate change is likely to exacerbate a range of determinants that drive tuberculosis, the world's leading cause of death from a single infectious agent. However, tuberculosis is often neglected in wider climate health discussions. Commissioned by WHO, we developed an analytical framework outlining potential causal relationships between climate change and tuberculosis. We drew on existing knowledge of tuberculosis determinants, identified determinants likely to be sensitive to the effects of climate change, and conceptualised the mechanistic pathways through which these effects might occur. We collated evidence for these pathways, but found no studies directly linking climate change and tuberculosis, warranting research to build evidence for action. Nevertheless, the available indirect evidence supports the existence of plausible causal links between climate change and tuberculosis. This evidence highlights the need to consider tuberculosis as a climate-sensitive disease, and include tuberculosis in climate risk adaptation and mitigation programmes, and climate-resilient funding and response mechanisms. Only through urgent research and comprehensive action can we address this overlooked intersection and ensure that climate change does not become a barrier to ending the global tuberculosis epidemic.